Canine circovirus: an emerging virus of dogs and wild canids - Farzad Beikpour; Arash Letafati; Zahra Ahmadi Fakhr; Nicoal Decaro; Sayed-Hamidreza Mozhgani (Irish Veterinary Journal)
Abstract Canine Circovirus (CanineCV) is an emerging viral pathogen affecting dogs and wild canids worldwide. Belonging to the Circoviridae family, CanineCV exhibits genetic variability and has been associated with various clinical manifestations, including gastroenteritis, respiratory symptoms, and neurological disorders. While its prevalence is notable, gaps persist in understanding its pathogenicity and evolutionary origins. CanineCV often co-infects with other canine viruses, complicating diagnosis and treatment. Prevention strategies are hindered by the lack of targeted vaccines and the virus's resilience in the environment. This review paper summarizes the current knowledge on CanineCV and discusses the virus's genetic features and taxonomy, epidemiology in both domestic and wild populations, clinical manifestations, diagnosis methods, and prevention strategies. Additionally, the article highlights gaps in knowledge regarding CanineCV's pathogenicity, evolutionary aspects, and potential zoonotic transmission risks. Overall, it underscores the importance of further research to better understand and mitigate the impact of CanineCV on canine health and public health.